When Do Nigerian Women of Reproductive Age Initiate and What Factors Influence Their Contraceptive Use? A Contextual Analysis - Ekholuenetale M; Olorunju S; Fowobaje KR; Onikan A; Tudeme G; Barrow A (Dove Medical Press, 2021)
Michael Ekholuenetale,1 Samson Olorunju,1 Kayode R Fowobaje,1 Adeyinka Onikan,2 Godson Tudeme,3 Amadou Barrow4 1Department of Epidemiology and Medical Statistics, Faculty of Public Health, College of Medicine, University of Ibadan, Ibadan, Nigeria; 2Program Management Unit, Management Sciences for Health, Abuja, Nigeria; 3School of Medicine, College of Medical Sciences, University of Benin, Benin City, Edo State, Nigeria; 4Department of Public & Environmental Health, School of Medicine & Allied Health Sciences, University of The Gambia, Kanifing, The GambiaCorrespondence: Amadou Barrow Email abarrow@utg.edu.gmBackground: Contraceptive use initiation and continuation is one of the major interventions for reducing maternal deaths worldwide. Nigeria aimed to achieve a 27% prevalence rate of modern contraceptive uptake by 2020, however, this seems to have remained unachieved. The objective of this study was to investigate when Nigerian women initiate contraceptive use and its associated factors, using nationally representative data.Methods: Data on 11,382 Nigerian women (aged 15- 49 years) from the 2017 Performance Monitoring and Accountability 2020 (PMA2020) survey were used to determine the prevalence of lifetime contraceptive use. The Kaplan-Meier test was used to determine median time (years) to contraceptive uptake. In addition, the factors associated with contraceptive use were determined using multivariable logistic regression model. Statistical significance was determined at 5%.Results: The prevalence of modern contraceptive use was 14.2%. There were disparities in the timing (years) of contraceptive use initiation across several women's characteristics. Women from urban residence, highest household wealth index, nulliparous, unmarried, and highly educated women had the minimum median time (years) to contraceptive use initiation. The multivariable logistic model showed that rural women were 26% less likely to initiate contraceptive use, when compared with the urban dwellers (OR= 0.74; 95% CI: 0.65, 0.84). Furthermore, married women were 24% less likely to initiate contraceptive use, when compared with the unmarried (OR= 0.76; 95% CI: 0.63, 0.93). In addition, geographical region, wealth, television source, ever given birth, education, age, and religion were significantly associated with contraceptive use.Conclusion: The prevalence of contraceptive use is low in Nigeria. There were differences in contraceptive use initiation among women of reproductive age in Nigeria. There is a need to adopt sustainable strategies to improve contraceptive uptake and to re-iterate the benefits of contraception, including providing enlightenment programs among key populations such as the rural dwellers and low income earners.Keywords: inequality, family planning, PMA2020, FP2020, Nigeria, contraceptive use